An Influence of Advancing Technology on Students’ Reading and Writing Proficiency - Parmar, Nilambari; Sadhu, Maun (Journal of Ecohumanism, 2025)
The rapid advancement of technology has significantly altered educational practices and expectations, particularly in reading and writing. This study investigates the influence of evolving technology on students’ proficiency in these critical areas. With the proliferation of digital tools such as laptops, tablets, and internet resources, the traditional classroom landscape has been transformed, impacting both instructional strategies and students’ learning experiences. The study focuses on middle school students, a demographic increasingly exposed to digital technology. The literature review provides a theoretical framework for understanding the intersection of technology and literacy skills. At the same time, interviews and surveys offer practical insights into how technology is implemented in educational settings and its perceived effects on students’ reading and writing capabilities. Findings reveal a generally positive impact of technology integration on students’ literacy skills. Digital tools have facilitated diverse reading and writing practices, promoting greater engagement and personalized learning opportunities. Teachers report improvements in students’ ability to access, analyze, and produce text, suggesting that technology can enhance writing skills and support reading comprehension through interactive and multimedia resources. However, the study also identifies a growing dependency on technology, with concerns about potential distractions and the diminishing emphasis on traditional literacy practices. In conclusion, while advancing technology presents numerous benefits for enhancing students’ reading and writing proficiency, it also necessitates a balanced approach to avoid over-reliance.